FIGURE OF VASYL STEFANYK IN THE CONTEXT OF MEMOIRS LITERATURE OF WESTERH UKRAINE OF THE FIRST HALF OF THE XXth CENTURE - Fedun, M. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article reads about the figure of Vasyl Stefanyk in the context of memoirs literature of Western Ukraine of the first half of the XX-th centure. Into consideration are taken flashbacks of Stefanyk and those about him of Ukrainians and the Polish (K. Grinevycheva, S. Pshybyshevskyi, V. Morachevskyi, D. Lukiyanovych etc). The subject of attention become obituaries about the writer. The idea about originality of Western Ukrainian memoir inheritance is proven.